GBA genotype-Parkinson’s phenotype correlation in a cohort of 252 Italian patients from the Tuscany region - Rodolfo Tonin; Silvia Ramat; Marina Rinaldi; Silvia Falliano; Federica Feo; Francesca Cardona; Camilla Matassini; Guido Mannaioni; Giulia Grigioni; Luca Caremani; Alessandra Govoni; Maria Luisa Della Bona; et al. (Clinical Parkinsonism & Related Disorders)
Introduction: heterozygous mutations in the glucocerebrosidase gene (GBA1), encoding the lysosomal enzyme β-glucocerebrosidase (GCase) are the most common genetic risk factor for Parkinson’s disease (PD). To assess the frequency of GBA1 variants related to PD in a cohort of Tuscany patients and to determine the link between GBA1 variants and motor and non-motor clinical features in PD. Methods: We screened GCase enzyme activity on Dried Blood Spot using tandem mass spectrometry (LC-MS/MS) and performed sequencing analysis on entire cohort of PD patients by Next Generation Sequencing (NGS) technology. Variants were confirmed with Sanger method. Results: among the 252 PD patients, we detected reduced GCase activity (≤5 μmol/h/L) in 78 (31%). NGS analysis identified 22 carriers of GBA1 variants (8.7%) in whom 14 carried common GBA1 variants currently known to be related to PD (Leu444Pro, Asn370Ser, Glu326Lys, Thr369Met and Asp409His). PD patients who were heterozygous carriers of pathogenic GBA1 variants presented with earlier onset of PD, faster disease progression and a more frequent non-motor symptoms compared to the remaining PD patients without GBA1 mutations. Conclusions: 8.7% of the 252 PD patients carried GBA1 variants at a heterozygous level, and their clinical presentation and progression were more severe compared to other patients within our cohort.